2021
DOI: 10.1111/psyg.12768
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hormone replacement therapy on cognitive function in healthy postmenopausal women: a meta‐analysis of 23 randomized controlled trials

Abstract: To investigate how hormone replacement therapy (HRT) intervention affects cognitive function in randomized controlled trials of healthy postmenopausal women, the PubMed and Web of Science databases were searched for relevant publications up to 1 May 2020. Random-effects, subgroup analysis, sensitivity analysis and meta-regression analyses were conducted with 23 selected publications. HRT had a significant negative effect on global cognition (standardized mean difference (SMD): À0.04, 95% confidence interval (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Similarly, an observational study showed that the introduction of HRT in midlife (age 48.7 years) was associated with a 26% reduced risk of dementia compared to 48% increased risk when HRT was initiated in later life (age 76 years) [80]. In a recent meta-analysis in healthy post-menopausal women, HRT use was associated with reduced global cognition, which was less evident for those younger than 60 years old [17]. Our results are consistent with these findings, with our findings specifically observing that this impact of early initiation is specific to APOE4 carriers.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Similarly, an observational study showed that the introduction of HRT in midlife (age 48.7 years) was associated with a 26% reduced risk of dementia compared to 48% increased risk when HRT was initiated in later life (age 76 years) [80]. In a recent meta-analysis in healthy post-menopausal women, HRT use was associated with reduced global cognition, which was less evident for those younger than 60 years old [17]. Our results are consistent with these findings, with our findings specifically observing that this impact of early initiation is specific to APOE4 carriers.…”
Section: Discussionmentioning
confidence: 96%
“…A recent meta-analysis of 23 RCTs showed no impact of oral estrogen alone or CEE plus MPA on delayed memory scores, even at a younger age (<60 years), with an overall negative effect on global cognition. However, no sub-group analysis according to APOE genotype was carried out [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low bioavailable levels of estradiol in older women were associated with a higher risk of cognitive impairment 7 . However, results of randomized clinical trials that examined postmenopausal hormone therapy for prevention of cognitive decline have found no benefits 8,9 . These inconsistent findings could stem from different reasons including locally generated estrogen that affects brain function 10 above and beyond circulating estrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, these trials were not successful. Previous randomized controlled trials (RCTs) tended to focus on hormones ( 44 , 45 ) and rarely considered hormone transporters such as SHBG. Our MR research systematically interpreted the relationship between SHBG and neurodegenerative diseases, extending traditional observational associations to gene-mediated causality.…”
Section: Discussionmentioning
confidence: 99%